Military training and camps of the Pan Africanist Congress of South Africa, 1961-1981 (Historia, 2021)
This article focuses on two aspects of the exile history of the Pan Africanist Congress of South Africa (PAC) that have thus far been poorly researched, namely its military training and its military camps. The article seeks to demonstrate the impact of the leadership of the PAC on the type of training provided to recruits in South Africa and in other countries; and secondly, on life and conditions in its most significant military camps in exile. It is argued that the leadership of the PAC, and in particular the conflicts that characterised its history for most of the exile period, were largely responsible for the limited attention given to military training and operations, and for insufficient support from the international community for the PAC's armed struggle and military camps.  Hierdie artikel fokus op twee aspekte van die ballingskap geskiedenis van die Pan Africanist Congress van Suid-Afrika (PAC) wat tot nou toe swak nagevors is, naamlik sy militêre opleiding en kampe. Die artikel poog om die impak van die leierskap van die PAC op die tipe opleiding wat gegee word aan rekrute in Suid-Afrika en in ander lande, en die lewe en omstandighede in sy belangrikste militêre kampe in ballingskap te demonstreer. Daar word aangevoer dat die leierskap van die PAC, en in die besonder die konflikte wat sy geskiedenis gekenmerk het vir die meeste van die ballingskap tydperk, was grootliks verantwoordelik vir die beperkte aandag wat aan militêre opleiding en operasies gegee word, en vir onvoldoende ondersteuning van die internasionale gemeenskap vir die PAC se gewapende stryd en militêre kampe.
Keywords: Kinkuzu; Poqo; Militere kampe; ANC Exiles; Tanzanie; Pan Africanist Congress (PAC)